Luminescent properties of tri-cellulose acetate composites doped with rare earth terbium (III) complex. Issue 1 (January 2014) - Liu, Xiang; Zhu, Jiang; Xu, Zhaozan
Abstract : Rare earth terbium (III) ternary complexes were synthesized using acrylic acid (AA) or 5-sulfosalicylic acid (SSA) as the first ligand and 1, 10-phenanthroline (Phen) as the second ligand. Tri-cellulose acetate (TCA)/Tb(AA)3 Phen or TCA/Tb(SSA)3 Phen composites were prepared by means of solution blend, and their luminescent properties were investigated by fluorescence spectrophotometer. The luminescence spectra of TCA/Tb(AA)3 Phen and TCA/Tb(SSA)3 Phen composites display the characteristic excitation and emission bands of terbium ions and suggest some influence of the TCA matrix on luminescent properties of the terbium complexes. The maximum excitation peak at around 343 nm for the Tb(SSA)3 Phen system is redshifted for 14 nm, compared with 329 nm for the Tb(AA)3 Phen system, which is correlated to the electron-donating/attractive groups of ligands. In the range of doping concentration of the Tb(AA)3 Phen complex (1, 2 and 5 wt.%) or the Tb(SSA)3 Phen complex (1, 2, 3 and 5 wt.%), emission intensities increase with the increment of corresponding doping concentration and concentration quenching effect has not taken place.